Problems of the procedural status of a juvenile participant in criminal proceedings (Journal of actual problems of jurisprudence, 2020)
Juvenile delinquency as a social phenomenon, as well as the problems of criminal proceedings involving minors, is relevant for objective reasons. Psycho-physiological features of a minor’s personality determine the specifics of legal regulation of criminal procedural legal relations, through the prism of observing his (her) rights and obligations and achieving the goals of justice. The aim of this research is to develop an inclusive mechanism for ensuring the rights of juveniles in criminal proceedings, by improving the procedural status of a minor suspect (accused, defendant), a witness who has the right to defense, a victim witness, and to develop a unified approach to the status of a minor. In order to solve the tasks set in this article, the composition of participants in criminal proceedings was analyzed through the prism of the scope of their procedural rights and obligations, and thus, significant differences in the procedural status of minor participants in criminal proceedings were identified, which potentially create risks of violation of their rights. As a result, minors may in practice be deprived of the rights proclaimed at the normative level due to the lack of procedural possibilities in their implementation. The paper presents well-founded proposals for improving legislation and judicial and investigative practice in this direction. Theoretical and practical usefulness of the study is that the formation of a unified approach to the status of a minor, regardless of the procedural position he occupies in the criminal process, is designed to give a positive practical result. This will be reflected in overcoming terminological problems and forming a unified practice of legal proceedings in criminal cases involving minors and thus also in real protection of the rights of minors in criminal proceedings. Key words: juvenile (minor), procedural status of a minor, juvenile justice, minor suspect, victim, witness, guarantees of rights, representation of interests of minors.